Kulturpolitikkens nodvendighed? Hovedtraek i dansk kulturpolitik - Schab, Sylwia (Folia Scandinavica Posnaniensia, 2007)
The article introduces the cultural policy issues in Denmark. It covers the most important foundations and developmental trends of the Danish cultural policy from the sixties to the nineties. This period is divided into decades according to the particular developmental phases which present the issues specific to these phases.